2006
DOI: 10.1207/s15327558ijbm1304_9
|View full text |Cite
|
Sign up to set email alerts
|

Social support and behavior in a stressful situation in relation to myocardial infarction and mortality: who is at risk? results from prospective cohort study “men born in 1914,” malmö, sweden

Abstract: Coronary heart disease remains an important cause of morbidity and mortality. Much data support the view that social support is associated with coronary heart disease. Participants of the study "Men born in 1914," (414 men) were followed from a baseline measurement in 1982/83 until the end of 1996. At baseline, the men answered a questionnaire on social support and participated in a stressful test where their behavior was categorized as adaptive or maladaptive. This study examined whether social support had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
0
25
0
1
Order By: Relevance
“…Social interactions with others have been linked to improved mental health (Dalgard et al, 1995;Dressler, 1985;Mathiesen et al, 1999); to lower susceptibility to cancer (Ell et al, 1992;Hibbard and Pope, 1993;Welin et al, 1992), infectious diseases (Cohen, 1991;Lee and Rotheram-Borus, 2001;Patterson et al, 1996) and cardiovascular diseases (Johnson and Hall, 1988;Lepore et al, 1993;Roy et al, 1998); and to lower overall and cause-specific mortality rates (Andre-Petersson et al, 2006;Berkman et al, 1992;Brummett et al, 2005;Hanson et al, 1989;Lyyra and Heikkinen, 2006;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Social interactions with others have been linked to improved mental health (Dalgard et al, 1995;Dressler, 1985;Mathiesen et al, 1999); to lower susceptibility to cancer (Ell et al, 1992;Hibbard and Pope, 1993;Welin et al, 1992), infectious diseases (Cohen, 1991;Lee and Rotheram-Borus, 2001;Patterson et al, 1996) and cardiovascular diseases (Johnson and Hall, 1988;Lepore et al, 1993;Roy et al, 1998); and to lower overall and cause-specific mortality rates (Andre-Petersson et al, 2006;Berkman et al, 1992;Brummett et al, 2005;Hanson et al, 1989;Lyyra and Heikkinen, 2006;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Prior epidemiological studies have demonstrated that having a small social network and lack of social support are associated with an increased incidence of coronary heart disease 58 and heart failure 6,9 , but relatively few studies have examined whether these factors are associated with incident stroke 1013 . The mechanisms underlying these associations have not been fully elucidated but likely include both behavioral factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the social support protective role. However, some results point out that the beneficial effect from the support provided is especially significant in men (André‐Petersson, Hedblad, Janzon, & Östergren, ; Krumholz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This could be especially significant for coping strategies or adjustment to disease where the literature is less conclusive (Brink et al, ; Wiklund et al, ). Finally, it was also expected that perceived social support would have a more direct role in life satisfaction reported by men than by women after a serious health problem (André‐Petersson et al, ; Kristofferzon, Löfmark, & Carlsson, ). This result was tested to see if it could be explained by the possible mediation of the social support and satisfaction relationship by adjustment strategies to disease.…”
Section: Introductionmentioning
confidence: 99%